A study on Proton and its challenges after AFTA / Judy Asing - Asing, Judy (2008)
The objective of this study is to analyse the business response taken by the national automaker, Perusahaan Otomobil Nasional Berhad or PROTON in the face of regional market liberalization with the implementation of AFTA (Asean Free Trade Area) not only in Malaysia but also in the Asean region. The study encompasses Proton's initial growth, and market share which are mainly in the local market, and the eventual effects that affected Proton with the abolishment of the trade tariff. This also includes the various steps taken by Proton over several years, such as the investments in the technology for product, i.e. research and development (R & D), model varieties, and quality in preparation of AFTA. The study explicates the evident of efforts from Proton itself to succeed in the automotive industry. Proton had responded positively to the implementation of AFTA by considering its limitations and had taken the necessary steps to overcome its weaknesses. AFTA had also provided greater opportunities for Proton to venture further into the exports market in the Asean region. Proton's new high-tech R & D (with Computer Aided Design (CAD)) had produced several new models of cars that had made in-roads to the Asean regional markets, notably to Thailand, Indonesia and Vietnam. Proton's success in the regional Asean market would enable Proton to penetrate further in the world markets to compliment its success in the U.K. and the Australian markets.